Advanced Operating Strategies to Extend the Applications of Simulated Moving Bed Chromatography. Issue 12 (12th October 2017) - Kim, Kyung-Min; Lee, Ju Weon; Kim, Sunhee; Santos da Silva, Francisco Vitor; Seidel-Morgenstern, Andreas; Lee, Chang-Ha
Abstract: Chromatographic separation with solid stationary and fluid mobile phases is widely used to isolate and purify compounds. One of the most productive improvements in preparative chromatography is the simulated moving bed (SMB) process, which enables continuous feed supply and product removal by periodic operation of a multicolumn to simulate a countercurrent flow between the phases. The SMB process produces high‐purity compounds, even with low selectivity, and offers higher productivity and lower eluent consumption than batch chromatography. Recently, intensive efforts have been made to expand the range of applications through the design, modeling, and optimization of the SMB process to produce advanced operating strategies, which are described and evaluated in this review. Abstract : The simulated moving bed process is considered as one of the most productive improvements in preparative chromatography, by periodic operation of a multicolumn to simulate a countercurrent flow between the phases. Advances in this process are described with a focus on introducing novel concepts and providing examples and advantages of recently proposed operating strategies in specific areas.